Benefit of Bed Raising to Manage Acid Sulphate Soil Under Industrial Forest Plantations Area - Ali Martinus; Dwi Setyawan; Yuanita Windusari (Sriwijaya Journal of Environment, 2019)
Industrial Forest Plantations (IFP) are intended to increase the productivity non-productive natural forest production. In South Sumatra Province IFP is widely developed in wetlands; one of them is in acid sulphate soils which have major problems with flooding and waterlogging. To solve this problem, the technology other than  making drainage canals is Bed Raising. Bed Raising is to make beds to facilitate the implementation of planting, maintenance and harvesting, in addition to maintaining good soil aeration conditions. However, Bed Raising on acid sulphate soil raises a new problem is pirite oxidation, which affects the chemical properties of acidic sulphate soil. The purpose of this study was to see the benefits of bed raising in the management of acid sulphate land in IFP areas. This study uses survey methods and data are presented in tabulations. The results of this study indicate that the benefits of bed raising in the management of acid sulphate land are no longer flooded or waterlogging. While the results of chemical analysis of soil in bed raising plots are very acidic soil pH (pH <3), Al-dd saturation is very high (> 70%), and high pyrite concentration (> 2.4%). This value is not suitable for plant growth.